Pengaruh Lingkungan Kerja Fisik Dan Gaji Terhadap Kinerja Karyawan Pada KSP Credit Union Bererod Gratia Pusat Jakarta Timur - Marlo Anthony Sahanaya; Lidya Pricilla (Kampus Akademik Publiser, 2026)
Abstract This study aims to analyze the influence of the Physical Work Environment and Salary on Employee Performance, both partially and simultaneously, at KSP Credit Union Bererod Gratia East Jakarta Center. The research background is based on the condition of the physical work environment that still requires improvement in several aspects and a relatively uniform salary structure that does not fully consider the workload and responsibilities of each position. The type of research used is associative quantitative with a survey method. The research population consisted of all 60 permanent employees, all of whom were used as the sample (census). Data was collected through a Likert scale 1-5 questionnaire and analyzed using multiple linear regression analysis with the help of SPSS 27 software. The hypothesis testing results show that: (1) Partially, the Physical Work Environment has no significant effect on Employee Performance (sig. 0.801 > 0.05). (2) Partially, Salary has a positive and significant effect on Employee Performance (sig. 0.001 < 0.05). (3) Simultaneously, the Physical Work Environment and Salary together have a positive and significant effect on Employee Performance (F sig. 0.000 < 0.05) with a contribution of 35.4% (R Square = 0.354). Based on these findings, it is concluded that although the physical work environment is not yet the main individual driver, the combination of improving the quality of the physical work environment and a fair and competitive salary system is an effective strategy for improving employee performance. The suggestions provided are that management needs to review the salary structure based on workload and responsibilities, as well as periodically maintain and improve physical work environment facilities, while still paying attention to other non-financial factors that influence performance.